A new species of Mimonecteola (Crustacea: Amphipoda: Hyperiidea: Mimonecteolidae) from the Southern Ocean - Zeidler, Wolfgang (Zootaxa, 2012)
A new species of Mimonecteola, M. antarctica sp. nov., is described from two specimens collected by the R/V Eltaninfrom the Amundsen Sea (Pacific Sector) and north-west of Elephant Island (Atlantic Sector). It is most similar to M. carls-bergi Zeidler, 2009 but is readily distinguished by the relatively shorter, and more feeble, fifth pereopoda and the relatively longer second antennae. The genus now consists of seven species and a new key to distinguish them is provided.